The Effect of Camphor on the Male Mice Reproductive System - Nikravesh, Mohammad Reza; Jalali, Mohammd (Urology Journal, 2009)
Purpose: In Iranian traditional medicine there is a belief that camphor is a suppressor of sexual activity. Based on this idea and since there are few studies on this issue, we evaluated the effect of camphor on histopathological changes of reproductive system in young male mice of balb/c racial type. Materials and Methods: Thirty-six premature male balb/c mice, were divided into 3 paired groups of experimental, control, and sham (n = 6). Experimental groups 1 and 2 received 30 mg/kg camphor dissolved in olive oil (orally) for 10 and 20 days, respectively. The control groups received the same volume of olive oil during the same periods of time, and no intervention was done in sham groups. All groups were kept in the same environmental condition. At the end of exposure time, each group was anesthetized and their testes were removed for obtaining serial sections, and histological staining. Results: Comparing to the control groups less vascularization in testis tissue of experimental groups was seen. Furthermore, using stereological methods demonstrated that internal diameters of seminiferous tubules in experimental groups were significantly smaller than those in control groups (P < 0.005). Also, the number of released sexual cells was lower in experimental groups (P < 0.005). No meaningful difference was seen between controls and sham groups. Conclusion: Administration of camphor and its effects on male mice reproductive system may result in significant structural changes, including vascularization and proliferation of sexual cells. This can affect maturation of seminiferous tubules and subsequently, reproductive function of testes in mice.